Changing utilization of Stavudine (d4T) in HIV‐positive people in 2006–2013 in the EuroSIDA study1. Issue 9 (18th May 2015) - Podlekareva, D; Grint, D; Karpov, I; Rakmanova, A; Mansinho, K; Chentsova, N; Zeltina, I; Losso, M; Parczewski, M; Lundgren, JD; Mocroft, A; Kirk, O; et al.
<x xml:space="preserve">Abstract</x> Objectives The long‐term side effects of stavudine (d4T) led to recommendations in 2009 to phase out use of this drug. We aimed to describe temporal patterns of d4T use across Europe. Methods Patients taking combination antiretroviral therapy (cART) in EuroSIDA with follow‐up after 1 January 2006 were included in the study. cART was defined as d4T‐containing [d4T plus at least two other antiretrovirals (ARVs) from any class] or non‐d4T‐containing (at least three ARVs from any class, excluding d4T). Poisson regression was used to describe temporal changes in the prevalence of d4T use and factors associated with initiating d4T. Results A total of 5850 patients receiving cART on 1 January 2006 were included in the current analysis, rising to 7768 patients on January 1 2013. During this time, the prevalence of d4T use fell from 11.2% to 0.7%, with an overall decline of 19% per 6 months [95% confidence interval (CI) 19–20%]. d4T use declined fastest in Northern Europe [26% (95% CI 23–29%) per 6 months], and slowest in Eastern Europe [17% (95% CI 16–19%) per 6 months]. In multivariable Poisson regression models, new d4T initiations decreased by 14% per 6 months [adjusted incidence rate ratio (aIRR) 0.86; 95% CI 0.80–0.91]. Factors associated with initiating d4T were residence in Eastern Europe (aIRR 4.31; 95% CI 2.17–9.98) versus other European regions and HIV RNA > 400 copies/mL (aIRR 3.11; 95% CI 1.60–6.02) versus HIV RNA < 400 copies/mL. Conclusions d4T use has declined sharply since 2006 to low levels in most regions; however, a low but persistent level of d4T use remains in Eastern Europe, where new d4T initiations post 2006 are also more common. The reasons for the regional differences may be multifactorial, but it is important to ensure that all clinicians treating HIV‐positive patients are aware of the potential harmful effects associated with d4T.